Os recursos educacionais abertos e a (re) significação do livro didático: uma análise semiótica discursiva do movimento “software livre” na educação pública - Karlla Andrea Leal Cruz (2021)
In the present work, research-action, with an interpretative bias, we sought to dialogue with a didactic project, whose products constituted the corpus of this investigation. Two perspectives coexist: that of a teacher and a researcher, where both poles (school and academy) come together. This dissertation sought to understand, from the experience in the classroom, how Digital Information and Communication Technologies (DICTs) have been assumed by the school, as well as the place of Textbooks in relation to this movement. Our research also discussed the conception of closed educational materials whose licenses respond to the market need, but not to the interest of teachers and students or to the public character of school institutions. We covered the Open Educational Resources (OER) movement, which can give new meaning to school practices, presenting several justifications for an effective adoption of these teaching, learning, research and extension materials in public basic education. To do so, we analyzed the insertion of DICTs in the skills and competences of the education guiding documents, BNCC (2018), and “Percursos Curriculares e Trilhas de Aprendizagem para a Rede Municipal de Educação de Belo Horizonte em Tempos de Pandemia” (2020), with focus in the mother tongue curriculum, and in the Portuguese language textbooks: pré-BNCC (2018), “Para viver juntos: português 8º ano” (2017), and pós-BNCC (2018), “Geração alpha língua portuguesa 9º ano” (2020), adopted, respectively, for the 2017-2018-2019 and 2020-2021-2022 trienniums. Our quantitative and qualitative approach was based on epistemological constructions about the movement of free education and OER in Brazil. We demonstrated that Open Educational Resources can become a complementary solution for a more collaborative, customized, inclusive, accessible and democratic educational movement. We carried out the application of a Didactic Project, which evidenced the movement beyond the “author” and “reader” dichotomy towards the concomitance in “coauthors”, verifying different forms of open digital manifestations as potential complementary pedagogical instruments. We believe that free and non-paid science possibly inserted in Elementary School, in non-federative public schools, enables the democraticity that permeates OER, making educational and informational products flow, which can add knowledge both for the school, the university and for the society. In this way, it is not a question of research about the other and for the other, but rather an endogenous one, about us and which turns to ourselves. Finally, we analyzed, under the bias of French semiotics (elementary and discursive level), some comments from students in an Open Educational Resource, at the event “Universidade EAD e Software Livre” Congresso UEADSL 2019. Documentary and semiotic analyses demonstrated that new practices with complementary learning objects, they generate a displacement of individuals whose discursive constructions point to the field of affection, enunciation and self-reflection. In summary, we sought to analyze the Open Educational Resources (OER) as a complementary didactic proposal to the Textbook: a discursive analysis of the Free Software Movement through a semiotic bias.